Conceptualizing the Malay World: Colonialism and Pan-Malay Identity in Malaya, by Soda Naoki - Norizan Kadir (Kajian Malaysia, 2026)
The history of Malay nationalism during British colonialism has been rigorously studied by many scholars from multifaceted aspects; however, it has never reached a plateau or dead end. This topic has always fascinated scholars who are interested to reconstruct the historical experience by using different methods and approaches. The findings seem to be not straightforward but rather, complex and paradoxical. Malay nationalism would never have been achieved without the significant role of education. The British government used vernacular education as a powerful weapon to control the minds of the Malays and thus sustain its colonialism in Malaya. J.S. Furnivall (1948, 393) was undoubtedly right with his analysis: “it is pleasanter and cheaper to mould a literate population by appropriate and intelligent methods of education than to suppress an illiterate mob by machine guns.” However, one can never anticipate the impact of education towards the colonised people, whose minds and hearts were never the same as those of their colonial master.